Pengelolaan Hutan Berbasis Kearifan Lokal dan Pengembangan Hutan Desa di Mukim Lutueng Kecamatan Mane Kabupaten Pidie Provinsi Aceh - Ainul Mardhiah; Supriatno Supriatno; Djufri Djufri (Universitas Islam Negeri Ar-Raniry, 2016)
The forest area in Pidie District was decreased by illegal logging, forest conversion, mining and road construction without regard to environmental aspects.This study aims to (1) knewabout local wisdom in Qanun Mukim Lutueng about forest management (2) knew the potential development of community forest in Mukim Lutueng (3) analyzed the community perceptions and behaviours about forest conservation. This study was conducted on 1 October 2015 to 30 April 2016in Mukim Lutueng, Pidie District, Aceh Province. The research method is ethnography with Participatory Rural Appraisal (PRA). The result shown thatLocal wisdom in forest management consist of the law in forest activities management, suggestion and prohibition, and local community of forest management. The potential development of community forest support by civil society organizations (NGOs) with community empowerment and government community institution. Perceptions and behaviours towards qanun implementation and community forest in Mukim Lutueng was strong perceptions and with strong attitudes especially shown by community people in three villages; Mane, Lutueng and Blang Dalam. Meanwhile, the communitypeople of Turue Cut showed the weak level of perceptions and attitudes towards the qanun implementation and community forest in Mukim Lutueng. The community law (qanun) threatened by illegal gold mining activities and illegal logging. Community people need an alternative economythat does not rely on the resources of the forest.